On the taxonomic state of water mite taxa (Acari: Hydrachnidia) described from the Palaearctic, part 3, Hygrobatoidea and Arrenuroidea with new faunistic data - Smit, Harry; Gerecke, Reinhard; Pešić, Vladimir; Gledhill, Terence (Zootaxa, 2015)
Following revision of material from museum collections and recent field work, new taxonomic and faunistic data are given for several representatives of the water mite superfamilies Hygrobatoidea and Arrenuroidea.